Is intravenous iron sucrose the treatment of choice for pregnant anemic women?. Issue 3 (20th November 2012) - Devasenapathy, Niveditha; Neogi, Sutapa Bandyopadhyay; Zodpey, Sanjay
Abstract Anemia during pregnancy remains an important public health problem in developing countries like India. Anemia is the direct cause of 12–15% of maternal deaths. Iron deficiency is the commonest cause for anemia in the Indian subcontinent. Several preventive and therapeutic approaches are in practice. The available routes of iron supplementation are oral and intravenous. In spite of oral iron being least invasive, cheap and safe, the ineffectiveness of oral iron due to dietary inhibitors and poor compliance are well known. Intravenous iron sucrose can be a promising therapy for moderate to severely anemic pregnant women and has been in practice for quite some time in private and public health practices. In this article, we report the current evidence on the safety and efficacy of intravenous iron sucrose in anemic pregnant women on hematological and clinical outcomes. Though the evidence on its efficacy in improving hemoglobin and serum ferritin is convincing, its effect on maternal and fetal outcomes are unclear. This is primarily due to lack of well‐designed and larger studies powered to detect difference in clinical outcomes. Hence, there is a need to gather evidence from a well‐designed large randomized clinical trial conducted in a developing country. The results of such a study would feed into the national policy and would form the basis to frame guidelines for management of anemia in developing countries.